THE PERSISTENCE OF EUROPE AS THE MEASURE OF MODERNITY: NOTES ON THE HABERMASIAN EPIC - Oliveira, Marcos de Jesus (Faculdade de Filosofia e Ciências, 2018)
The objective of the present work is to present the relations between Eurocentrism as an imperial cognitive pattern and the social thought of Jürgen Habermas. Initially, we will discuss the presuppositions implicit in the Habermasian theorization of modernity: its philosophy of history and its spatial-geographical assumptions. Such an analysis will be carried out by discussing the comparative method quite common to the tradition of the European social sciences and whose use in Habermas shows his vision on Europe as the norm, a measure of all other societies and civilizations of the world. Following the objective outlined, two works were chosen: one from the early 1980 and the other from the beginning of the 21st century in order to show how the Habermasian narrative remains attached to what we call European imperial cognitive pattern from which it is possible to see a geopolitics of world population classification.